2011
DOI: 10.1002/anie.201102982
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Aromaticity out of Aromatic Interactions

Abstract: What's in a name? The phrase “aromatic interactions” is widely used to describe noncovalent interactions involving aromatic rings. However, computed stacking energies suggest that disruption of the aromatic π delocalization can enhance many of these interactions and also render them orientation‐dependent. Because of these effects, the use of nonaromatic systems should be advantageous in supramolecular chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 31 publications
8
157
0
Order By: Relevance
“…19 Wheeler has questioned the importance of aromaticity in associations between aromatic systems. 20 Egli, in the course of reviewing nucleic acid-intercalator interactions, alternatively proposed that the terms should be even more broadly defined to include any near-space interaction involving aromatic rings, even when they do not interact in a parallel fashion, and even when the other functional group involved is not aromatic.…”
Section: -7mentioning
confidence: 99%
“…19 Wheeler has questioned the importance of aromaticity in associations between aromatic systems. 20 Egli, in the course of reviewing nucleic acid-intercalator interactions, alternatively proposed that the terms should be even more broadly defined to include any near-space interaction involving aromatic rings, even when they do not interact in a parallel fashion, and even when the other functional group involved is not aromatic.…”
Section: -7mentioning
confidence: 99%
“…Although these interactions are often collectively referred to as "aromatic interactions", we note that aromaticity of the interacting species is not a requirement for these interactions. Indeed, Bloom and Wheeler [3] recently showed that aromaticity actually hinders some p-stacking and anion/p interactions, although it can enhance cation/p interactions.…”
Section: Introductionmentioning
confidence: 98%
“…[88] Reedijk and coworkers [89] built upon this work after observing a different complex of NO 3 À with triazine in a crystal structure. Using BLYP, Reedijk et al showed [89] that although the roughly centered motif shown in Figure 13 is lower in energy, there is a local energy minimum in which NO 3 À is positioned over the side of the ring and tilted toward the center, analogous to the arrangement observed in their crystal structure. [89] Alkorta et al [90] reported MP2 and B3LYP energies for anion/ p interactions between various halides and polyatomic anions, including cyanide anion, with perfluorinated benzene, pyridine, furan, thiophene, and naphthalene.…”
mentioning
confidence: 95%
“…For discussion on aromatic interactions, see: Bloom & Wheeler (2011);Martinez & Iverson (2012). For graph-set motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…No significant weak non-covalent crystal packing interactions involving centroids of planar rings are observed. Though it has become an acceptable norm in describing weak non-covalent interactions in terms of C-H···π and π···π interactions, some recent views (Martinez & Iverson, 2012;Bloom & Wheeler, 2011) on these interactions calls for a careful analysis while describing them in crystal structures.…”
Section: S1 Commentmentioning
confidence: 99%